Sharia Supervisory Board, Audit Committee, And Corporate Social Responsibility Disclosure - A. Dola Bastina; Yustrida Bernawati (Jurnal Akuntansi, 2019)
This study examined the influence of the Sharia Supervisory Board and Audit Committee on the corporate social responsibility disclosure. The research sample used in the study is Islamic Banks in Indonesia from 2014 to 2018, with a total of 60 banks. Quantitative methods with multiple linear regression data analysis techniques were used in this study. The testing of hypotheses uses Ordinary Least Square (OLS) regression with a significance of 1%, 5%, and 10%. Test F shows a model that stable and significant. The results of this study supported the research hypothesis that ACSIZE brought a positive and significant effect on corporate social responsibility disclosure. In addition, the sharia supervisory board and the audit committee meet not influence the corporate social responsibility disclosure.